FEATURES OF USING THE WORDWALL SERVICE IN THE EDUCATIONAL PROCESS OF AN OUT-OF-SCHOOL EDUCATION INSTITUTION - Tarasova, Tetyana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article describes the possibilities of the online service Wordwall when used in the educational process. Examples from the experience of using exercises created with the help of the service in the educational process of the municipal institution «Center for Scientific and Technical Creativity of Student Youth» of the Kherson Region are give. The advantages and disadvantages of using the online service Wordwall are described.